2012
DOI: 10.1260/2040-2295.3.4.587
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Ergonomic Issues in the Laparoscopic Operating Room

Abstract: This review paper discusses the ergonomic challenges associated with laparoscopy in the operating room (OR) and summarizes the practical ergonomic solutions. The literature search was conducted in the fields of laparoscopy and applied ergonomics. Findings indicated that laparoscopic OR staff (surgeons, perioperative nurses and technicians) commonly experienced physical and mental ergonomic risks while working in prolonged static and awkward body positions. This study highlighted the need for more ergonomic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 73 publications
(132 reference statements)
0
21
0
Order By: Relevance
“…Due to the high prevalence of musculoskeletal problems among the studied surgical team members, the reduction of occupational injury after laparoscopic procedures requires awareness, knowledge, and commitment to ergonomic guidelines. Katrin et al reported that almost all their participants (94.4%) were unaware of the existing guidelines about table height and monitor and instrument positioning during endoscopic surgeries (1). Similar findings were also highlighted by Gofrit et al (24).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Due to the high prevalence of musculoskeletal problems among the studied surgical team members, the reduction of occupational injury after laparoscopic procedures requires awareness, knowledge, and commitment to ergonomic guidelines. Katrin et al reported that almost all their participants (94.4%) were unaware of the existing guidelines about table height and monitor and instrument positioning during endoscopic surgeries (1). Similar findings were also highlighted by Gofrit et al (24).…”
Section: Discussionmentioning
confidence: 64%
“…Based on some studies, more than half of the surgeons prefer to use manual control instead of the pedal because of its discomfort and consequences. Monitor's position is another major ergonomic factor leading to improper use of the pedal (1,25). Unfortunately, as some operating rooms in this study had only one monitor, first assistants and operating room nurses had to turn the monitor to have a good view.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The MIS environment contains a greater number and larger pieces of equipment that occupy more space in the OR. This may limit the working area as well as access to the patient 1 . The equipment required is increasingly complex and technologically advanced.…”
Section: Continuing Education: Guideline Implementation: Minimally Inmentioning
confidence: 99%
“…Positioning of the monitors to provide optimal viewing and eliminate ergonomic discomfort for both surgeon and team is paramount. The large size of the equipment and potential for collisions of the overhead lights with the monitors has prompted many facilities to build and redesign their rooms to address these issues 1,11 …”
Section: Continuing Education: Guideline Implementation: Minimally Inmentioning
confidence: 99%